2016
DOI: 10.1002/mds.26584
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Nigral Hyperintensity on 3 Tesla MRI of Parkinsonism: Comparison With 123I‐FP‐CIT SPECT

Abstract: The loss of nigral hyperintensity on susceptibility-weighted imaging suggested nigrostriatal dopaminergic degeneration in a large portion of patients with parkinsonism, which was indicated by (123) I-2β-carbomethoxy-3β-(4-iodophenyl)-N-(3-fluoropropyl)-nortropane single photon emission computerized tomography. In consideration of false-negative and -positive cases, well-designed imaging protocols should be introduced to improve the performance of nigral hyperintensity imaging. © 2016 International Parkinson an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
112
3
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(124 citation statements)
references
References 27 publications
3
112
3
6
Order By: Relevance
“…) . Subsequent studies using 3T MRI have also been able to replicate this finding in most PD patients (refer to Table for list of studies) . This replication has generated considerable interest to use nigrosome imaging as a way of studying and diagnosing nigral pathology in PD.…”
Section: Nigrosome Imagingmentioning
confidence: 80%
See 1 more Smart Citation
“…) . Subsequent studies using 3T MRI have also been able to replicate this finding in most PD patients (refer to Table for list of studies) . This replication has generated considerable interest to use nigrosome imaging as a way of studying and diagnosing nigral pathology in PD.…”
Section: Nigrosome Imagingmentioning
confidence: 80%
“…The nigrosome abnormality also correlates with nigrostriatal dopaminergic dysfunction as detected by DAT SPECT. The absence of dorsolateral nigral hyperintensity in PD subjects predicted ipsilateral striatal DAT signal abnormality with a sensitivity of 87.5% (95% CI, 83.5%–90.7%) and specificity of 83.6% (95% CI, 77.6%–88.2%) …”
Section: Nigrosome Imagingmentioning
confidence: 99%
“…The 3 studies each included subjects with APDs or subjects with parkinsonism and normal dopaminergic radiotracer imaging . Data on these subjects with non‐PD parkinsonism were not included in the meta‐analysis because of an insufficient number of studies (≥4 studies needed for the meta‐analysis as described later), but analyzed descriptively.…”
Section: Methodsmentioning
confidence: 99%
“…Most patients with PD or other types of neurodegenerative parkinsonism studied so far lack DNH at least unilaterally (see Fig. A) . Although current evidence thus suggests that this novel MRI feature may be a marker for PD, available studies have mostly involved small samples and had heterogeneous control populations.…”
mentioning
confidence: 99%
“…However, because the absence of this finding also was observed in all patients with PSP and in 83 of 90 patients with PD, its clinical usefulness in differentiating between different causes of neurodegenerative parkinsonism is questionable, although it seems to be specific for neurodegenerative parkinsonism . Another recent study also showed that the loss of dorsolateral nigral hyperintensity is observed in patients with neurodegenerative parkinsonism, including MSA; furthermore, it corresponds to presynaptic dopaminergic imaging with a concordance rate of 86.2% …”
Section: Mri Findings Of Msamentioning
confidence: 98%